Different interactomes for p70‐S6K1 and p54‐S6K2 revealed by proteomic analysis. Issue 20 (12th September 2016) - Pavan, Isadora C. B.; Yokoo, Sami; Granato, Daniela C.; Meneguello, Letícia; Carnielli, Carolina M.; Tavares, Mariana R.; do Amaral, Camila L.; de Freitas, Lidia B.; Paes Leme, Adriana F.; Luchessi, Augusto D.; Simabuco, Fernando M.
Abstract : S6Ks are major effectors of the mTOR (mammalian target of rapamycin) pathway, signaling for increased protein synthesis and cell growth in response to insulin, AMP/ATP levels, and amino acids. Deregulation of this pathway has been related to disorders and diseases associated with metabolism, such as obesity, diabetes, and cancer. S6K family is composed of two main members, S6K1 and S6K2, which comprise different isoforms resulted from alternative splicing or alternative start codon use. Although important molecular functions have been associated with p70‐S6K1, the most extensively studied isoform, the S6K2 counterpart lacks information. In the present study, we performed immunoprecipitation assays followed by mass spectrometry (MS) analysis of FLAG‐tagged p70‐S6K1 and p54‐S6K2 interactomes, after expression in HEK293 cells. Protein lists were submitted to CRAPome (Contaminant Repository for Affinity Purification) and SAINT (Significance Analysis of INTeractome) analysis, which allowed the identification of high‐scoring interactions. By a comparative approach, p70‐S6K1 interacting proteins were predominantly related to "cytoskeleton" and "stress response, " whereas p54‐S6K2 interactome was more associated to "transcription, " "splicing, " and "ribosome biogenesis." Moreover, we have found evidences for new targets or regulators of the S6K protein family, such as proteins NCL, NPM1, eIF2α, XRCC6, PARP1, and ILF2/ILF3 complex. This study provides new information about the interacting networks of S6Ks, which may contribute for future approaches to a better understanding of the mTOR/S6K pathway.